Determinants of Behavioral Intention toward Digital Health Services in India: A PLS-SEM Study on the e-Sanjeevani Application - Amar, Amar; Malik, Komal; Srivastava, Namita; Parashar, Neha (International Review of Management and Marketing, 2025)
The rapid digitization of healthcare services has driven the adoption of telemedicine platforms, particularly in developing countries like India. The e-Sanjivani application, a government-backed telemedicine service, has gained prominence, yet the determinants influencing user behavioral intention toward its adoption remain underexplored. This study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to investigate key factors—performance expectancy, effort expectancy, social influence, price value, and user satisfaction—that shape users’ behavioral intention to use the e-Sanjivani application. The study is based on survey data collected from a diverse sample across urban and semi-urban regions of India. Findings indicate that performance expectancy, effort expectancy, social influence, and price value significantly influence user satisfaction, which, in turn, is a strong predictor of behavioral intention. While effort expectancy plays a role, its impact is relatively lower. The study highlights the necessity of enhancing the application's usability, affordability, and social endorsement to drive widespread telemedicine adoption. Policymakers and healthcare providers can leverage these insights to optimize digital health strategies, ensuring equitable and sustainable telemedicine integration in India. Future research should explore longitudinal trends and extend the scope to rural populations to refine telemedicine implementation strategies further.